Community Engagement through Interactive Field-Based Activities - Casale , Carolyn; Thomas , Adrainne (Experiential Learning and Teaching in Higher Education, 2022)
This qualitative case study consisted of social justice interactive field-based experiential learning activities designed to understand community partnerships between a university and local public school. The research question was: How can interactive field-based activities build closer community ties? The theoretical foundation incorporated Ken Zeichner’s “hybrid spaces” with the premise of field-based interactive experiences. The findings indicated the need for further activities that create partnerships between teacher education programs and neighboring public schools.